Diffusion tensor imaging point to ongoing functional impairment in HIV-infected children at age 5, undetectable using standard neurodevelopmental assessments - Ackermann, Christelle (AIDS Res Ther, 2020)
BACKGROUND: Perinatal HIV infection negatively impacts cognitive functioning of children, main domains affected are working memory, processing speed and executive function. Early ART, even when interrupted, improves neurodevelopmental outcomes. Diffusion tension imaging (DTI) is a sensitive tool assessing white matter damage. We hypothesised that white matter measures in regions showing HIV-related alterations will be associated with lower neurodevelopmental scores in specific domains related to the functionality of the affected tracts. METHODS: DTI was performed on children in a neurodevelopmental sub study from the Children with HIV Early Antiretroviral (CHER) trial. Voxel-based group comparisons to determine regions where fractional anisotropy and mean diffusion differed between HIV+ and uninfected children were done. Locations of clusters showing group differences were identified using the Harvard–Oxford cortical and subcortical and John Hopkins University WM tractography atlases provided in FSL. This is a second review of DTI data in this cohort, which was reported in a previous study. Neurodevelopmental assessments including GMDS and Beery-Buktenica tests were performed and correlated with DTI parameters in abnormal white matter. RESULTS: 38 HIV+ children (14 male, mean age 64.7 months) and 11 controls (4 male, mean age 67.7 months) were imaged. Two clusters with lower fractional anisotropy and 7 clusters with increased mean diffusion were identified in the HIV+ group. The only neurodevelopmental domain with a trend of difference between the HIV+ children and controls (p = 0.08), was Personal Social Quotient which correlated to improved myelination of the forceps minor in the control group. As a combined group there was a negative correlation between visual perception and radial diffusion in the right superior longitudinal fasciculus and left inferior longitudinal fasciculus, which may be related to the fact that these tracts, forming part of the visual perception pathway, are at a crucial state of development at age 5. CONCLUSION: Even directed neurodevelopmental tests will underestimate the degree of microstructural white matter damage detected by DTI. The visual perception deficit detected in the entire study population should be further examined in a larger study.